European collaboration on health technology assessment: looking backward and forward. (19th April 2022) - Ruether, Alric; Imaz-Iglesia, Iñaki; Bélorgey, Chantal; Lo Scalzo, Alessandra; Garrett, Zoe; Guardian, Marcus
Abstract: The establishment of health technology assessment (HTA) has been an important topic in Europe for many years. There have been a series of activities starting with first projects in 1994 leading to joint actions from the European Network of HTA (EUnetHTA) ending in 2021. This long interval of engagement with HTA structures, methodology, and processes by all member states led to a reliable basis for European collaboration in HTA. This article shows milestones and developments from EUR-ASSESS in 1994 through the progress of EUnetHTA and the accompanying EU-HTA-Network up to the recent elaboration of the EU-HTA-Regulation. With the EU-HTA-Regulation HTA collaboration is taken out of the trial phase of more than 15 years. Through the previous EU HTA collaboration, the appreciation and understanding of the differences and complexities behind the HTA processes in the EU healthcare systems have improved. It is now necessary to make the final steps toward a sustainable European Network for HTA.